Co-operative groups in their environments : a population-ecological model for co-operative membership and performance - Lasowski, Ophir; Justus Liebig University Giessen (My University, 2010)
The aim of this work is to develop an alternative evolutionary approach to assessing the performance of co-operative organizations. The focus of investigation is turned to the co-operative organization as a group of members in a market environment containing non-members. Significant unique features of the co-operative organization is illustrated at first. After reviewing historical aspects of evolution theories and their positioning in biology, economic and social sciences, alternative notions of evolution and the osmosis of ideas is suggested. Further on, a concept for the evolutionary function of exit, voice and acquiesce strategies in social contexts is developed analog to the biological concept of fight, flight or cope reactions. Leaning on the known social and group-psychological features of the co-operative organizations species, and on the assumption of membership rationality at the individual members level, a theory of exit, voice or acquiesce decisions, and the influence of the groups size on their results, is being introduced. A following empirical dynamic model will utilize the previous recognitions achieved, to demonstrate the effect of ommanent restrictions to group-growth. Moreover it is being proven, that the co-operative organization can still be considered as successive, in the populations ecological as well as in the social sense, even if it is not growing. A corrected approach to the utilization of group growth as indicator for co-operative performance is suggested as a result.

Ziel dieser Arbeit ist die Entwicklung eines alternativen evolutionären Ansatzes zur Bewertung der Leistung genossenschaftlicher Organisationen. Im Mittelpunkt der Untersuchung steht die genossenschaftliche Organisation als Gruppe von Mitgliedern in einer aus Nicht-Mitgliedern bestehenden Marktumgebung. Einleitend werden für die Untersuchung elementare Eigenschaften der genossenschaftlichen Organisation geschildert. Nach einer Übersicht historischer Aspekte der Evolutionstheorien und ihrer Positionierung in der Biologie, den Wirtschafts- und Sozialwissenschaften, wird eine neue Vorstellung der Evolution und der Osmose von Ideen vorgeschlagen. Weiterhin wird ein Konzept für die evolutorischen Funktionen der strategischen Abwanderung/ Widerspruch/ Duldung in sozialen Zusammenhängen, als Analogie zum biologischen Konzept von Fight, Flight or Cope-Reaktionen präsentiert. Anlehnend an anerkannten sozialen und gruppenpsychologischen Eigenschaften der Genossenschaften und an die Annahme der Rationalität der Mitgliedschaft auf der Ebene des individuellen Mitglieds, wird eine Theorie über Abwanderung, Widerspruch und Duldung, und über den Einfluss der Gruppengröße auf deren Ergebnis, vorgestellt. Die zuvor erarbeiteten Erkentnisse werden im Anschluss in einem empirisch dynamischen Model umgesetzt, um die Wirkung immanenter Restriktionen des Gruppenwachstums zu demonstrieren. Weiterhin wird bewiesen, dass genossenschaftliche Organisationen weiterhin als erfolgreich beurteilt werden dürfen, sowohl im populationsökologischen als auch im sozialen Sinn, auch wenn sie kein Wachstum aufweisen. Ein weiterentwickelter Ansatz zur Anwendung des Gruppenwachstums als Indikator für genossenschaftliche Leistung wird als Resultat der Untersuchung vorgeschlagen.
Genossenschaftliche Gruppen in ihren Umwelten : ein populationsökologisches Modell für Genossenschaftsmitgliedschaft und -performanz
Keywords: Evolutionsökonomie; Populationsökologie; Organisationswachstum; Abwanderung-Widerspruch; Fight Flight; Economic Evolution; Populations Ecology; Organizational Growth; Exit Voice; Fight Flight; ddc:630